Relationships for Fundamental Interactions Between Aquatic Plants and Contaminants in Oxidation Pond (OP) Via Phytogreen System - Abdul Syukor, Abd Razak (2015)
Phytogreen, previous name Lestari is the process of phytoremediation by which plants are used to remove or stabilize hazardous pollutants that exist in soil, sediments, surface water or groundwater. Phytogreen provides a very effective and comparatively low cost way to extract, detoxify or immobilize a wide variety of contaminants such. Today, Phytogreen or known as ‘Green Technology for the Future’ is a new technology to stabilize wastewater that has been produce.